Phase formation, microstructure and setting time of MCM-48 mesoporous silica nanocomposites with hydroxyapatite for dental applications: Effect of the Ca/P ratio. Issue 15 (15th October 2017) - Lenji, Razieh Karimi; Nourbakhsh, Amir Abbas; Nourbakhsh, Nosrat; Nourbakhsh, Mahtab; Mackenzie, Kenneth J.D.
Abstract: Nanocomposites of MCM-48 mesoporous silica and hydroxyapatite (HA) are investigated as possible alternatives for the commonly used Mineral Trioxide Aggregate (MTA) dental cement, and the effect of their Ca/P ratio on their structure, properties and setting times is reported. XRD, FTIR and EDS/SEM analysis of the nanocomposites indicate that crystalline HA is formed within the mesoporous silica structure. High Ca/P ratios lead to the formation of free CaO within the nanocomposite, decreasing its setting time; the shortest setting time ( 40 min), which occurs in the MCM-48/HA nanocomposite with a Ca/P ratio of 5, in physiological saline solution, is considerably shorter than the setting time of MTA ( 140 min under identical conditions). Thus, the shorter setting time of the MCM-48/HA nanocomposites, coupled with their lack of toxicity, high degree of bioactivity and their stability in tissue fluids, suggest that they could serve as a useful replacement for MTA.